Probiotics and synbiotics supplementation improve glycemic control parameters in subjects with prediabetes and type 2 diabetes mellitus: A GRADE-assessed systematic review, meta-analysis, and meta-regression of randomized clinical trials. (October 2022) - Naseri, Kaveh; Saadati, Saeede; Ashtary-Larky, Damoon; Asbaghi, Omid; Ghaemi, Farahnaz; Pashayee-Khamene, Fereshteh; Yari, Zahra; de Courten, Barbora
Abstract: Probiotics and synbiotics have been proposed to exhibit an important role in glucose homeostasis and maintain the balance of the gut microbiota. However, clinical trials have shown mixed findings. Therefore, we conducted a systematic review and meta-analysis of all eligible randomized controlled trials (RCTs) examining the effects of probiotics and synbiotics intake on glycemic outcomes among individuals with prediabetes and type 2 diabetes mellitus (T2DM). The PubMed/Medline, Scopus, ISI Web of Science, and Cochrane library were searched up to March 2022 for published RCTs exploring the effectiveness of probiotics and synbiotics compared to control on glycemic outcomes. The random-effects model was applied in order to the estimation of 95 % confidence interval (CI) and the weighted mean difference (WMD) for each endpoint. Meta-analysis of forty-six RCTs (3067 participants) showed that probiotics and synbiotics supplementation significantly reduced fasting plasma glucose (FPG) (weighted mean difference (WMD): − 11.18 mg/dl, 95 % CI: − 13.60, − 8.75, p ˂0.001), fasting insulin serum level (WMD: −1.23 µIU/ml, 95 % CI: −1.76, −0.71, p ˂0.001), hemoglobin A1c (HbA1c) (WMD: −0.35 %, 95 % CI: −0.44, −0.26, p˂0.001), and homeostatic model assessment of insulin resistance (HOMA-IR) (WMD: −0.87, 95 % CI: −1.09, −0.65, p˂0.001). Additionally, probiotics and synbiotics intake resulted in an increase in values of quantitative insulin-sensitivity check index (QUICKI) (WMD: 0.01, 95 % CI: 0.00, 0.01, p˂0.001). However, probiotics and synbiotics consumption did not change glucose values following oral glucose tolerance test (OGTT). Our findings suggest that probiotic and synbiotic intake has favorable effects on glycemic profile in patients with prediabetes and T2DM. Graphical Abstract: ga1